Pubertal anthropometry in sons and daughters of women with preeclamptic or normotensive pregnancies. Issue 11 (1st July 2009) - Ogland, B; Vatten, L J; Romundstad, P R; Nilsen, S T; Forman, M R
Abstract : Objective: To compare body mass index (BMI) and waist and hip circumference in early puberty (10.8 years in girls and 11.8 years in boys) among offspring of preeclamptic and normotensive pregnancies. Design: Population based follow-up study. Methods: Anthropometry measured in early puberty in 91 girls and 92 boys of preeclamptic pregnancies, and in 194 girls and 166 boys of normotensive pregnancies, with similar anthropometric measures among mothers, performed at the beginning of the index pregnancy, and at follow-up, when their offspring were in early puberty. Results: Among girls, the preeclampsia group had higher body mass (BMI 18.3 kg/m 2 vs 17.5 kg/m 2, p = 0.01) and larger waist circumference (63.7 cm vs 61.6 cm, p = 0.05) compared to the normotensive group, but the differences were restricted to the offspring of mothers with a high body mass (BMI >30 kg/m 2 ). Among boys, we observed no differences in anthropometric measurements between groups. Conclusions: The higher BMI and larger waist of daughters of women with preeclampsia was only present if their mothers were obese. These results suggest that preeclampsia in obese women may lead to a distinct disadvantage in body size for their daughters in early puberty.